HUMAN DEVELOPMENT NETWORK INLITERATURE FROM 2020 TO 2023 - Campas, Celia Yaneth Quiroz (IPHO-Journal of Advance Research in Science And Engineering, 2024)
The literature from 2020 to 2023 suggests that human and sustainable development are concomitant.The objective of this work was to establish the relationship between human and sustainable development. A cross-sectional, exploratory and correlational study was carried out with a sample of 100 students selected for their professional profile. The results show the prevalence of the environmental and social dimension as nodes of centrality and grouping. In this sense, the hypothesis that relates human development to environmental development is not rejected and a significant difference between the theoreticalnetworksof relationships with respect to the observations of this work is accepted. In addition, the delimitation of the studyto the learning of human and sustainable development in its environmental and social dimensions is recommended